The structural, electronic and thermal transport properties of pentagonal MS2 (M = Zn, Cd) monolayers: A first-principles study. (August 2022) - Pan, Lu; Zhang, Tian; Hu, Cui-E; Chen, Xiang-Rong; Geng, Hua-Yun
Abstract: Two-dimensional (2D) pentagonal materials have attracted tremendous interest due to their multifunctional applications in catalytic, optoelectronic and thermoelectric fields. In the work, we examine the dynamic and thermal stabilities for the pentagonal MS2 (M = Zn, Cd) monolayers by phonon spectra and ab initio molecular dynamics simulations. The structural, electronic and thermal transport properties of the pentagonal MS2 (M = Zn, Cd) monolayers are investigated by employing first-principles calculations coupled with Boltzmann transport theory. The pentagonal MS2 (M = Zn, Cd) monolayers exhibit the semiconductor character with indirect band gaps. The high carrier mobility with 553 cm 2 V −1 s −1 of CdS2 monolayer is obtained along the y direction. The calculated anisotropic lattice thermal conductivities ( K l ) are 2.23 (1.83) and 5.69 (5.27) W/m K along x ( y ) direction for the pentagonal ZnS2 and CdS2 monolayers at 300 K, respectively. The heat capacity, phonon group velocity and phonon lifetime are also obtained. It is found that the lower K l along the same direction ( x or y ) can be attributed to the stronger phonon anharmonicity. A similar anisotropy of power factor (PF) for pentagonal MS2 (M = Zn, Cd) is discussed in detail. Additionally, the zT values of 1.09 and 0.96 are predicted for the pentagonal ZnS2 and CdS2 at the n-type doping along the y direction at 300 K, suggesting the potential applications in thermoelectric fields of pentagonal MS2 (M = Zn, Cd) monolayers. Highlights: The ZnS2 and CdS2 monolayers show the semiconductor character with indirect band gaps. The obtained lattice thermal conductivities are lower than many other 2D materials at 300 K. The maximum ZT values of 1.09 and 0.96 are predicted for the ZnS2 and CdS2 at 300 K.